Use of tartaric acid for the production of sustainable Portland-free CSA-based mortars. (20th May 2018) - Coppola, L.; Coffetti, D.; Crotti, E.
Highlights: Sustainable OPC-free mortars with CSA and SCMs were investigated. Tartaric acid acts as superplasticizer and set-retarding admixture. Shrinkage and mechanical properties are influenced by tartaric acid addition. About 60% reduction in Gross Energy Requirement and CO2 emissions was achieved. Abstract: The purpose of the study is to evaluate the effect of a tartaric acid-based set retarding admixture on rheological, elastic and physical performances of sustainable mortars manufactured with calcium sulfoaluminate, anhydrite and Supplementary Cementitious Materials replacing totally OPC. Experimental results indicated that the tartaric acid acts as superplasticizer and it is effective to extend the pot-life of mortars up to about 2 h. On the other hand, the set-retarding admixture provides a strong retardation of binder hydration resulting in a reduction of initial expansion and compressive strength at early ages. However, this retarding effect disappears at long ages.